2004
DOI: 10.4102/curationis.v27i3.995
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation and transplantation within the Zulu culture

Abstract: OpsommingGreater knowledge and technological advancement in the field of transplantation has increased the demand for organ donation beyond the supply of organs, espe cially among the black communities. This imbalance arises from the few sources of organs, limitations on the techniques of organ retrieval, disparities in the alloca tion of organs and socio-cultural factors. The aim of this study was to investigate the extent to which Zulu cultural norms and social structures influ ence an individual's decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…The present study demonstrated that as the number of bequests and donors increased, a reversal of the demographics of the cadavers occurred. As with organ donation, the reason for low numbers of bequeathed/donated cadavers from the SAA population may be due to religious and cultural beliefs (Kometsi and Louw, ; Bhengu and Uys, ). Similar reasons have been provided in Nigeria where religion, culture, ignorance and “love after death” prevent donations (EwonuBari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that as the number of bequests and donors increased, a reversal of the demographics of the cadavers occurred. As with organ donation, the reason for low numbers of bequeathed/donated cadavers from the SAA population may be due to religious and cultural beliefs (Kometsi and Louw, ; Bhengu and Uys, ). Similar reasons have been provided in Nigeria where religion, culture, ignorance and “love after death” prevent donations (EwonuBari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A striking finding that emerged from this analytical approach was the identification of thematically similar beliefs across culturally diverse study samples. The notion that organ donation interferes with funeral or burial rituals, for example, was identified in samples of: ethnic Asians living in Canada [29,30], the United Kingdom [14,24,35], and the United States of America [18]; the indigenous peoples of Canada [28] and the United States of America [22]; Zulu-speaking adults living in South Africa [17]; and individuals drawn from the general American [32], Australian [27], and Swedish [36] populations. These findings attest to the ubiquitous nature of many beliefs about organ donation and suggest that public health campaigns developed in one cultural context may also have relevance in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these concerns among African Americans include bodily integrity, the uncertainty of impeding resurrection of the body, and the lack of clarity about how death is determined (Gillman, 1999; Radecki & Jaccard, 1997). Because of these uncertainties and lack of information, people may defer to what they perceive as the stance of their religion and reject the idea of organ donation (Benghu & Uys, 2004). However, Christianity and many faiths not only support donation but also have supportive policy statements about it (Gallagher, 1998 ; Oliver, Woywodt, Ahmed, & Saif, 2010).…”
Section: Discussionmentioning
confidence: 99%